Study the sensitivity of M’sila city to the risk of flooding using geographic information systems - Brahimi, Hadjer; Amirache, Hamza (Journal of Human Sciences, 2021)
Algeria in general and the city of M’sila in particular, is considered one of the areas at constant risk of flooding, due to sudden and significant precipitation, leaving material and sometimes human losses. Its impacts are aggravated by unregulated construction on M’sila’s river, in the center and west of the city. The flood of 1994 and that of September 2007 are the biggest floods in the city, where the latter left 20 dead and more than 2 billion DA in material losses, due to rapid urban expansion and construction in non-building areas, as well as the sharp increase in population. The purpose of this article is mainly to identify the urban areas most at risk of flooding by using GIS in order to protect them in the future, and by enabling managers of up-to-date geographic information for efficiency in interventions.